Correction: Influence of digital banking channels on the number of branches in European Union countries and Serbia (2020, Vol. 56, No. 43, pp. 67-84) - Editorial Board (Anali Ekonomskog fakulteta u Subotici, 2020)
In the paper "Influence of digital banking channels on the number of branches in the European Union and Serbia" by Maja Putica, published in no. 43 (year 56) of the journal Annals of the Faculty of Economics in Subotica, on page 74, a wrong table was unintentionally published due to technical error, and on this occasion we apologize to the author and the readers. With the author’s consent, in this issue we publish the corrected page of the text and Table 2, which was originally supposed to be published on page 74.